105k views
3 votes
6. 2(h-8)- h= h - 16

a.8
b. -8
c. infinitely many solutions
d. no solution

i need the answer and a explanation of how to get my answer i need soon pls hurry

User Krishna V
by
4.4k points

2 Answers

6 votes

Hello from MrBillDoesMath!

Answer: c (infinitely many solutions)

Steps:

1) Simplify the original equation

2(h-8)- h= h - 16

2.As 2 (h-8) = 2h- 16, the equation in 1) is equivalent to

(2h-16) -h = h - 16

or

(2h-h) - 16 = h - 16

or

h - 16 = h -16

which is true for all values of h.

Regards, MrB

User Kishor Patidar
by
5.2k points
5 votes

Answer:

c. infinitely many solutions

General Formulas and Concepts:

Pre-Algebra

Distributive Properties

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Terms/Coefficients

Explanation:

Step 1: Define

Identify

2(h - 8) - h = h - 16

Step 2: Solve for h

  1. [Distributive Property] Distribute 2: 2h - 16 - h = h - 16
  2. Combine like terms: h - 16 = h - 16
  3. [Addition Property of Equality] Add 16 on both sides: h = h
User Bunnynut
by
4.8k points